Kinetic Modeling of Dye Effluent Biodegradation by Pseudomonas Stutzeri - Rajamohan, N.; Rajasimman, M. (Engineering, Technology & Applied Science Research, 2013)
Dye industry waste water is difficult to treat because of the presence of dyes with complex aromatic structure. In this research study, the biodegradation studies of dye effluent were performed utilizing Pseudomonas stutzeri in a controlled laboratory environment under anoxic conditions. The effects of operational parameters like initial pH of the effluent and initial Chemical Oxygen Demand (COD) of the effluent on percentage COD removal were studied. A biokinetic model is established giving the dependence of percentage COD removal on biomass concentration and initial COD of the effluent. The biokinetics of the COD removal was found to be first order with respect to both the microbial concentration and initial COD of the effluent. The optimal pH for better bacterial degradation was found to be 8.The specific degradation rate was found to be 0.1417 l/g Dry Cell Mass (DCM) h, at 320 C.